GASTROINTESTINAL FOOD ALLERGY IN CHILDREN - Svetlana G. Makarova; Leyla S. Namazova-Baranova; Elena A. Vishneva; Oksana A. Ereshko; Irina G. Gordeeva ("Paediatrician" Publishers LLC, 2017)
In recent years, there has been a significant increase in the prevalence  of food allergies. Pathological conditions associated  with a food intolerance are becoming an increasingly urgent problem of pediatrics. According to different researchers, allergic lesions of the gastrointestinal tract occurs in 25-50% of patients with such common pathology as an allergy to cow's milk proteins. The severity of diseases  associated  with food allergies and their prognosis  depend largely on early diagnosis and adequate treatment. Difficulties and errors  in the diagnosis  of gastrointestinal  food allergies  are associated  with both subjective  and objective  reasons,  primarily due to the fact that gastrointestinal  reactions to food are often delayed and non-IgE-mediated. The article describes clinical forms of gastrointestinal food allergy according to the existing classification. Diagnostic algorithms and modern approaches  to differential diagnosis of disease based on evidence-based  medicine and corresponding to international consensus papers are given.